2014
DOI: 10.1016/j.dsr.2013.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in the vertical distribution and community structure of Antarctic macrozooplankton and micronekton

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues.Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited. b s t r a c tThe macrozooplankton and micronekton community of the Lazarev Sea (Southern Ocean) was investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 84 publications
(131 reference statements)
3
47
0
2
Order By: Relevance
“…meso-and macrofauna dwelling at the sea ice-water interface layer. Previous research has shown that the community near the sea ice-water interface differs from the community in deeper water in terms of species composition and density, and community structure (Flores et al 2011(Flores et al , 2014. Typically, the surface community is integrated into the epipelagic community (White and Piatkowski 1993;Fisher et al 2004;Hunt et al 2011;Giesecke and González 2012).…”
Section: Introductionmentioning
confidence: 98%
“…meso-and macrofauna dwelling at the sea ice-water interface layer. Previous research has shown that the community near the sea ice-water interface differs from the community in deeper water in terms of species composition and density, and community structure (Flores et al 2011(Flores et al , 2014. Typically, the surface community is integrated into the epipelagic community (White and Piatkowski 1993;Fisher et al 2004;Hunt et al 2011;Giesecke and González 2012).…”
Section: Introductionmentioning
confidence: 98%
“…It should also be kept in mind that the RMT samples in the wake of the ship and therefore in disturbed sea ice conditions. Earlier comparisons of SUIT and RMT data also indicated that the RMT does not sample the ice-water interface well (Flores et al 2011(Flores et al , 2012a(Flores et al , 2014. Abundances calculated from the SUIT catch are probably underestimations due to the low efficiency of the SUIT to sample krill from sea ice crevices and over-rafted ice floes, where larval krill have been found to reside (Frazer et al 2002;Meyer et al 2009;Flores et al 2012b).…”
Section: Krill Population Structurementioning
confidence: 89%
“…Sub-adult and adult krill show variation in vertical migration behaviour and depth of occurrence, depending on region and season (Mauchline and Fisher 1969;Marr 1962;Pakhomov 1995;Watkins 2000;Flores et al 2012a;Siegel 2005). In a multi-seasonal study from the Lazarev Sea comparing the surface layer with deeper depth strata, the post-larval E. superba distribution patterns are variable and different from that of AC0 krill (Flores et al 2014). The trade-off of AC1 juveniles and (sub-) adults is likely different from that of larvae and AC0 juveniles due to, e.g., different (vertebrate) predators and/or food requirement (Quetin et al 1996;Siegel 2005;Flores et al 2012a).…”
Section: Comparison Of Different Depth Layersmentioning
confidence: 94%
See 2 more Smart Citations